2022
DOI: 10.3389/fpsyg.2022.865203
|View full text |Cite
|
Sign up to set email alerts
|

How Stress Can Change Our Deepest Preferences: Stress Habituation Explained Using the Free Energy Principle

Abstract: People who habituate to stress show a repetition-induced response attenuation—neuroendocrine, cardiovascular, neuroenergetic, and emotional—when exposed to a threatening environment. But the exact dynamics underlying stress habituation remain obscure. The free energy principle offers a unifying account of self-organising systems such as the human brain. In this paper, we elaborate on how stress habituation can be explained and modelled using the free energy principle. We introduce habituation priors that encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 105 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…If our goal beliefs cannot be met, then as a last resort, the goal itself may be changed. It has been shown that changing goal priors can indeed reduce uncertainty (Hartwig et al, 2022). However, changing goal priors comes at a significant cost, as we have to sacrifice our deepest preferences.…”
Section: Tolerable Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…If our goal beliefs cannot be met, then as a last resort, the goal itself may be changed. It has been shown that changing goal priors can indeed reduce uncertainty (Hartwig et al, 2022). However, changing goal priors comes at a significant cost, as we have to sacrifice our deepest preferences.…”
Section: Tolerable Stressmentioning
confidence: 99%
“…Those people who are uncertain in answering this question experience stress. Uncertainty is used here as 'entropy' in terms of information theory (Shannon, 1948) and means, in the context of stress, that even when people choose their most promising policy, they expect surprises, i.e., they remain uncertain about what will happen next (Hartwig et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations